Character Education in the Thought of Buya Hamka and Its Relevance in the Digital Era - Hanzalah, Muhammad; Harahap, Muhammad Yunan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: In the digital era, education and character formation have undergone profound transformations, presenting both unprecedented opportunities and significant moral challenges. While technological advancement enhances access to knowledge and communication, it simultaneously fosters risks of ethical degradation, individualism, and spiritual disorientation. The primary objective of this research is to critically examine Buya Hamka’s conception of religious character education and to assess its contemporary relevance in addressing the moral and spiritual dilemmas emerging within digital society. Methodology: The research employed a qualitative library study, using Buya Hamka’s works as primary sources and relevant scholarly literature as secondary references. Data were examined through content analysis to identify the core meaning of Hamka’s ideas and relate them to the contemporary digital context. Main Findings: Findings show that Hamka emphasized the integration of faith, intellect, and morality in shaping complete human beings. Faith is the moral foundation, intellect enables critical reasoning, and morality guides behavior. This model is especially relevant for the digital age, functioning as a moral filter against excessive information flow and instant culture. Hamka’s perspective demonstrates how Islamic values can provide balance between intellectual, moral, and spiritual needs. Novelty/Originality of this study: The study concludes that Hamka’s framework can be actualized through family, schools, society, and the use of digital technology. His thought is not only philosophical but also practical, offering a contextual model for strengthening the moral-spiritual identity of young generations amid globalization.